2001
DOI: 10.1093/ejo/23.6.695
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid bone position after surgical mandibular advancement

Abstract: A cephalometric evaluation of the changes in the horizontal and vertical placement of the hyoid bone and of those in the position of the head over the cervical spine after surgical mandibular advancement was undertaken. Seven linear and one angular measurement were investigated in 60 patients, 17 males and 43 females, before and one year after surgical mandibular advancement. The hyoid bone moved forwards horizontally in 78 per cent of the subjects, backwards in 17 per cent, and in 5 per cent of patients it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 17 publications
1
17
2
3
Order By: Relevance
“…Using cephalograms accumulated over 20 years in patients with mandibular deformation, Durzo et al 6) reported that the growth direction of the hyoid bone differed from that in healthy persons. Evaluating the position of the hyoid bone after anterior surgical movement of the mandibular bone, Gale et al 9) reported that the hyoid bone horizontally moved in the anterior direction along with the anterior movement of the mandibular bone.…”
Section: Introductionmentioning
confidence: 99%
“…Using cephalograms accumulated over 20 years in patients with mandibular deformation, Durzo et al 6) reported that the growth direction of the hyoid bone differed from that in healthy persons. Evaluating the position of the hyoid bone after anterior surgical movement of the mandibular bone, Gale et al 9) reported that the hyoid bone horizontally moved in the anterior direction along with the anterior movement of the mandibular bone.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 1,7,9,11,22,24 have shown that mandibular advancement results in changes to the position of the hyoid bone. The position of the hyoid bone after surgery may reflect stretching of the suprahyoid musculature and have an important role in maintaining the oropharyngeal airway space.…”
mentioning
confidence: 98%
“…LABANC and EPKER 11 reported immediate post-surgical movement of the hyoid bone in an anterior direction, but they emphasized the 'highly variable' nature of the post-surgical position of the hyoid. Most studies describe changes in hyoid bone position and pharyngeal airway size 1-2 years post surgery 1,7,9,11,23,24 .…”
mentioning
confidence: 99%
“…Suprahyoidal kas yapısının gerilimininazalmasıdabaşveboyundakikas yapısının dengesini değiştirebilir. Bu durum da,boyunkaslarıtarafındanoluşananteriora doğru bir kuvvet artışına neden olarak mandibulayı tekrar öne doğru itebilir (19). Eğer orofaringeal kompleks uzun süre bu şekilde bir etki yaratırsa, hyoid kemik pozisyonu ve suprahyoid kasların uzunluğu değişerek, iskeletsel relaps oluşabilir.…”
Section: A-positional Alterations Occurring At the Hyoid Bone And In unclassified
“…Therefore it has been introduced by several authorsthatanadaptiveextensivemovement occursinheadpostureaftersetbacksurgery toexpandtheairway.Thesecondimportant point is that the positional change at the hyoidboneaftermandibularsetbacksurgery whichcancauserelaxationofthesuprahyoid musculature. Reduction of the tension of suprahyoidal musculature can change the balanceofthemusculature.Thisprocesscan push the mandibula in anterior direction again by causing force increment anteriorly occurred by neck muscles (19). If the oropharyngeal complex produces effect as such long, skeletal relaps may occur by changing of the hyoid bone position and length of the suprahyoid muscles.…”
Section: C-solunum Yolu Obstrüksiyonuna Bağlımentioning
confidence: 99%